Pancreatic Tuberculosis Mimicking a Mass: A Case Report - Swaroopa Deme; Bhaskar Kakarla; Rajani Thakur; Purushotham Ramreddigari; Nageswara Rao Modugu (Case Reports in Clinical Practice, 2022)
Tuberculosis, a preventable and curable disease caused by Mycobacterium tuberculosis, is the leading infectious cause of mortality worldwide. Organs commonly affected are lungs and extrapulmonary organs like lymph nodes, meninges, bones, genitourinary and gastrointestinal tract. Ileocaecal tuberculosis is the commonest form of the gastrointestinal tract. Disseminated infection can involve almost all organs in the body but isolated pancreatic tuberculosis is rarely reported in the literature. Hereby, we report a case of a young female presenting with abdominal pain and further evaluation with imaging revealed pancreatic mass raising suspicion of malignancy. Endoscopic ultrasound (EUS) guided FNAC of pancreatic mass surprisingly revealed necrotizing granulomatous lesions favoring tuberculosis. This was further supported by the complete resolution of the mass with Antituberculous Therapy (ATT). What is important: All pancreatic masses are not malignant. Infectious causes like tuberculosis should be considered in the differential diagnosis which is curable by medication. With a high index of suspicion and adequate workup, unnecessary invasive procedures can be avoided.